To rewrite the expression \((3x−5)(2x+2)\) using the Distributive Property, we'll distribute each term in the first parenthesis by each term in the second parenthesis:
\[ (3x - 5)(2x + 2) = 3x(2x) + 3x(2) - 5(2x) - 5(2) \]
Calculating each part:
- \(3x(2x) = 6x^2\)
- \(3x(2) = 6x\)
- \(-5(2x) = -10x\)
- \(-5(2) = -10\)
Now we combine these results together:
\[ 6x^2 + 6x - 10x - 10 \]
Combining the like terms \(6x - 10x\):
\[ 6x^2 - 4x - 10 \]
So, the expression \((3x−5)(2x+2)\) rewritten using the Distributive Property is:
\[ \boxed{6x^2 - 4x - 10} \]